Ciguatera poisoning. Issue 5 (20th September 2007) - Achaibar, Kira C; Moore, Simon; Bain, Peter G
Abstract : Ciguatera is a form of poisoning that occurs after eating tropical and subtropical ciguatoxic fish. The ciguatoxins are a family of heat stable, lipid soluble cyclic polyether compounds that bind to and open voltage-sensitive Na + channels at resting membrane potential, resulting in neural hyperexcitability, as well as swelling of the nodes of Ranvier. The authors describe a 45-year-old man who developed acute gastrointestinal symptoms in Antigua soon after eating red snapper and grouper, potentially "ciguatoxic fish". This was followed by neurological symptoms 24–48 hours later, including temperature reversal (paradoxical dysaesthesia), intense pruritus and increased nociception as a result of a small fibre peripheral neuropathy. The patient's symptoms and small fibre neuropathy improved over a period of 10 months.